Var compensation by evolutionary programming considering unbalanced load and multiple harmonics in source voltage and load current - Pau, K. N.; Venkataseshaiah, C.; Ramar, K. (2009)
In modern distribution systems, power electronic loads generate a large amount of harmonic currents due to their non-linear load characteristics. With the increasing used of these non-linear loads, the source voltage and load current are becoming more distorted. This paper deals with VAr compensation considering multiple harmonics distortion in both source voltage and load current. The method uses evolutionary programming technique.